Analisis Beban Penerangan dan Daya Listrik untuk Perencanaan Sistem PLTS di Lapangan Sasmita Jaya - Widodo Rizki; Joko Tri Susilo (Jurnal Kajian dan Penelitian Umum, 2026)
Optimal lighting performance is crucial to support sports activities, especially in outdoor facilities operating at night. To improve energy efficiency and reduce dependence on conventional electricity sources, the implementation of Solar Power Plants (PLTS) is a viable alternative. This study aims to analyze the lighting load requirements and electrical power consumption at Sasmita Jaya Field as a basis for designing an appropriate solar power system capacity. The research methods include measuring lighting levels using a lux meter, collecting technical specifications for all lighting fixtures, calculating total installed power, and analyzing daily energy usage profiles. In addition, an evaluation of lighting conditions was conducted based on the Indonesian National Standard (SNI 03-6575-2001) for sports facilities to ensure adequate lighting quality. The results show that the main electrical load comes from the main lighting system, with daily energy consumption significantly affected by high nighttime operating hours. Based on the total energy demand and load profile, PLTS capacity planning is carried out by calculating daily energy requirements, solar panel derating factors, battery capacity, and the required inverter size. The recommended PLTS capacity is expected to meet lighting needs independently, reliably, and efficiently. The implementation of a solar power system at the Sasmita Jaya Field has the potential to reduce long-term operational costs, increase energy efficiency, and encourage the use of environmentally friendly renewable energy sources.